Coupled production and emission of short chain perfluoroalkyl acids from a fast developing fluorochemical industry: Evidence from yearly and seasonal monitoring in Daling River Basin, China. (November 2016) - Wang, Pei; Lu, Yonglong; Wang, Tieyu; Zhu, Zhaoyun; Li, Qifeng; Meng, Jing; Su, Hongqiao; Johnson, Andrew C.; Sweetman, Andrew J.
Abstract: Short chain perfluoroalkyl acids (PFAAs) have been developed since 2002 by the major manufacturers to replace the conventional C8 and higher homologues, with much of the world production shifted to China in recent years. In this study, we conducted a continuous monitoring program over the period 2011–2014 with seasonal monitoring in 2013 for PFAAs emitted from two rapidly developing fluorochemical industry parks located in the Daling River Basin, Northern China. The trend of PFAA contamination was identified, dominated by perfluorobutane sulfonic acid (PFBS), perfluorobutanoic acid (PFBA) and perfluorooctanoic acid (PFOA), with the maximum concentrations of 3.78 μg/L, 3.70 μg/L, and 1.95 μg/L, respectively. Seasonal monitoring uncovered the occasional emission of perfluorooctane sulfonic acid (PFOS). Construction trends of new facilities and associated manufacturing capacity of the main products were also analyzed to assess correlations with PFAA emissions. An assessment of the data over the period 2011–2014 found a positive correlation with fluorocarbon alcohol (FCA) production and emission of PFAAs. Groundwater and tap water around the main source indicated that the dominant PFAAs had different diffusion behaviors. PFBS levels were higher in surface water, while PFBA was dominant in groundwater and tap water, with PFOA levels being higher in downstream groundwater. Considering the continuous expansion and development of fluorochemical industry in the Daling River Basin, this study will provide abundant information on the effectiveness of risk assessment and management. Graphical abstract: Highlights: Various PFAA production processes and trends were identified. Emissions of PFAAs from fluorochemical industry parks are increasing. PFBS, PFBA and PFOA are the dominant PFAAs. PFBA levels increased more than PFBS and PFOA. PFBA was highly mobile in both river water and groundwater. Abstract : Increasing levels of PFBS, PFBA and PFOA in surface water were correlated with certain fluorochemical products, and influenced local ground water and tap water.